2018
DOI: 10.29244/jcds.3.1.59-69
|View full text |Cite
|
Sign up to set email alerts
|

Is it Parental Communication, Self-Esteem, or Internet use that makes Pornography Behavior in Teenagers? (cases of pornography and porno-action)

Abstract: <p class="Paragraf">Parent-adolescent communication will affect both positive and negative behaviors in adolescents. This study aims to analyze the influence of the characteristics of adolescents and families with parent-adolescent communication, self-esteem, the use of internet, pornography and porn-action.The respondents of the study were teenagers in the age groups of 14-17 years, consisted of 137 respondents in Bogor, selected by using random sampling technique.Parent-adolescent communication consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Pornography use in adolescence is often viewed as particularly concerning due to a combination of increasing sexual interest, high internet use, and the specifics of adolescent brain development (e.g., higher impulsivity and greater reward sensitivity; see Laili, Puspitawati, & Yuliati, 2018;Owens, Behun, Manning, & Reid, 2012). Compared to adults, these factors may make young people more vulnerable to adverse effects of pornography use.…”
Section: Pornography Use and Ppu In Adolescentsmentioning
confidence: 99%
“…Pornography use in adolescence is often viewed as particularly concerning due to a combination of increasing sexual interest, high internet use, and the specifics of adolescent brain development (e.g., higher impulsivity and greater reward sensitivity; see Laili, Puspitawati, & Yuliati, 2018;Owens, Behun, Manning, & Reid, 2012). Compared to adults, these factors may make young people more vulnerable to adverse effects of pornography use.…”
Section: Pornography Use and Ppu In Adolescentsmentioning
confidence: 99%
“…Pornografi adalah sebuah istilah untuk gambar, sketsa, ilustrasi, foto, tulisan, suara, gambar bergerak, animasi, kartun, percakapan, gerak tubuh, atau bentuk pesan lainnya melalui berbagai bentuk media komunikasi dan/atau pertunjukan di muka umum, yang memuat eksploitasi seksual yang melanggar norma kesusilaan dalam masyarakat (Kementerian PPPA, 2017). Sementara Na'am dan Wahyuningsih (dalam Laili, Puspitawati, & Yuliati, 2018) menjelaskan bahwa pornografi adalah aksi gerak tubuh, penonjolan bagian tubuh, menunjukkan alat vital dengan sengaja atau tidak, untuk merangsang seksual bagi yang melihat, baik secara langsung maupun melalui media. Sedangkan definisi dari Kor, et al (dalam Laili, Puspitawati, & Yuliati, 2018) pornografi adalah materi seksual eksplisit yang menggambarkan tubuh setengah telanjang atau telanjang yang melibatkan tindakan rangsangan genital/seksual.…”
Section: Landasan Teoriunclassified
“…A teenager who in essence is still unstable will be very easily influenced to things that smell of pornography. Sex material on the internet is so seductive and makes a giddy person easily snared, without feeling conscious they have been victimized (Efrati & Mikulincer, 2018;Fernandez, Tee, & Fernandez, 2017;Laili, Puspitawati, & Yuliati, 2018;Ly, Dwyer, & Fedoroff, 2018). From this opinion it can be concluded that the soul of a teenager who is still in a state of unstable and gamang will be very easily affected pornographic materials so that makes the moral values declined.…”
Section: The Effect Of Internet Abuse On Youth Moralmentioning
confidence: 99%
“…Thus, in adolescents will form the responsibility to be able to feel something experienced by others. Meanwhile, Furhmann suggests that adolescent moral development can be helped through educational efforts (Laili et al, 2018;Rodda et al, 2018). In addition to the this efforts, there are also several more attempts on the moral education of adolescents by educators, and counselors in particular (Dumais et al, 2016;Han, Park, & Thoma, 2018;Kollerová et al, 2018;Lelkes, Sood, & Iyengar, 2017): a) Please have an idols and a parent's example.…”
Section: Counselor's Position Educating Youth Moralsmentioning
confidence: 99%